Pengaruh Pijat Oksitosin Terhadap Intensitas Nyeri Pada Pasien Post Section Caesarea (SC) di RS Taman Harapan Baru Tahun 2025 - Jamilah Jamilah; Rita Rahmawati (Jurnal Ners, 2025)
Caesarean section (CS) often causes pain in the incision area and uterine contractions after birth. Post-CS pain management generally involves medication, which can have side effects. Oxytocin massage, which stimulates the release of the hormone oxytocin, can be an effective non-pharmacological alternative in reducing pain, reducing stress, and supporting smooth breastfeeding. This study aims to examine the effect of oxytocin massage on pain intensity in post-CS patients as a safer and more effective approach to pain management.To determine the effect of oxytocin massage on pain intensity in post-sectio caeserea (SC) patients at Taman Harapan Baru Hospital in 2025.The independent variable in this study is oxytocin massage, the dependent variable is pain intensity in post-sectio caeserea (SC) patients. The total respondents in this study were 30 respondents calculated based on data from mothers giving birth in CS at Taman Harapan Baru Hospital. Data analysis was carried out univariately and bivariately, using a paired sample t test sample t test if normally distributed and if not normally distributed using the Wilcoxon statistical test SPSS version 25.The Wilcoxon statistical test obtained the results that the majority of post-SC patients experienced a decrease in pain intensity, namely negative ranks as many as 30 respondents, so that the study obtained a p value of 0.000 which means that there is a difference before and after oxytocin massage on the pain intensity of post-SC patients.Virtual assistance by medical personnel through health applications to carry out oxytocin massage independently at home, and monitor their progress after therapy.